Mast Cell Activation Triggered by Retrovirus Promotes Acute Viral Infection - Song, Shu-Ting; Wu, Meng-Li; Zhang, Hai-Jiao; Su, Xiao; Wang, Jian-Hua (Frontiers in Microbiology, 2022)
Mast cells (MCs) are strategically located at the host-environment interface and their non-allergic roles in the immune-surveillance of pathogens have recently gained more attention. However, MC-caused detrimental regulation of immune inflammations can promote viral invasion. Currently, the role of MCs in retroviral infection remains elusive. We have recently proved that human gut MCs could capture and transfer HIV-1 to CD4+ T cells for promoting viral spread; MC-released histamine augments HIV-1-induced functional polarization of dendritic cells to cause immunosuppression via stimulating differentiation of regulatory T cells. In this study, we used a murine model of MuLV/Friend virus infection to address MC role in acute retroviral infection in vivo. The acute infection of MuLV/Friend virus could be established in C57BL/6 wild type mice, but viral acquisition showed low efficiency in C57BL/6-KitW−sh/W−sh (Sash) mice which lack MCs. In mechanism, we found that MuLV/Friend virus triggered MC activation for degranulation; MC degranulation subsequently activated the granulocyte-like myeloid derived suppressive cells (G-MDSCs) to inhibit CD8+ T cells- and NK cells-mediated antiviral immune responses. The reconstruction of MCs in Sash mice promoted acute retroviral infection by regulating G-MDSCs functions and antiviral immune responses. Importantly, the administration of MC stabilizers to block cell degranulation elevated antiviral immune response and consequently suppressed retrovirus infection. This study uncovers a specific role of MCs in acute retroviral infection and elucidates the underlying immune-mechanisms. Targeting MCs may provide a novel approach for controlling acute infection by retroviruses.